2024
DOI: 10.1039/d3nr04984a
|View full text |Cite
|
Sign up to set email alerts
|

In situ growth of a redox-active metal–organic framework on electrospun carbon nanofibers as a free-standing electrode for flexible energy storage devices

Zahir Abbas,
Nissar Hussain,
Surender Kumar
et al.

Abstract: The rational construction of free-standing and flexible electrodes based on redox MOF with CNF for electrochemical energy storage devices. The prepared electrode having flexibility at different angles and also utilized to enlighten LED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Pseudocapacitors (PCs) with rapid and reversible surface redox reactions and electrochemical adsorption/desorption of ions at the interface, commonly possessing greater specific capacity compared to electrical double-layer capacitors, have been extensively applied in smart grids, instant switches, emergency power, etc. The rational fabrication of pseudocapacitor electrode materials with good conductivity, rich active centers, and reasonable structure has been vital in constructing advanced supercapacitors. , Transition metal phosphides (TMPs) as n-type semiconductors with metalloid characteristics have raised significant attention as pseudocapacitive electrode materials because of the remarkable redox capability and high electrical conductivity generated by strong electron delocalization. Meanwhile, transition metal sulfides (TMSs), known for their ultrahigh theoretical capacitance and superior redox reversibility, have also been in the spotlight . However, the intrinsic slow oxidation–reduction reaction kinetics made TMPs and TMSs suffer from undesirable practical electrochemical performance. , Many works have demonstrated that the fabrication of TMP/TMS heterostructures with a unique morphology not only preserves component merits but also provides the potential synergistic effects to efficiently modulate the electronic structure, significantly narrow the band gaps, and then accelerate the kinetics of redox reactions. , Therefore, the integration of TMPs and TMSs is a promising strategy for developing advanced pseudocapacitive electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudocapacitors (PCs) with rapid and reversible surface redox reactions and electrochemical adsorption/desorption of ions at the interface, commonly possessing greater specific capacity compared to electrical double-layer capacitors, have been extensively applied in smart grids, instant switches, emergency power, etc. The rational fabrication of pseudocapacitor electrode materials with good conductivity, rich active centers, and reasonable structure has been vital in constructing advanced supercapacitors. , Transition metal phosphides (TMPs) as n-type semiconductors with metalloid characteristics have raised significant attention as pseudocapacitive electrode materials because of the remarkable redox capability and high electrical conductivity generated by strong electron delocalization. Meanwhile, transition metal sulfides (TMSs), known for their ultrahigh theoretical capacitance and superior redox reversibility, have also been in the spotlight . However, the intrinsic slow oxidation–reduction reaction kinetics made TMPs and TMSs suffer from undesirable practical electrochemical performance. , Many works have demonstrated that the fabrication of TMP/TMS heterostructures with a unique morphology not only preserves component merits but also provides the potential synergistic effects to efficiently modulate the electronic structure, significantly narrow the band gaps, and then accelerate the kinetics of redox reactions. , Therefore, the integration of TMPs and TMSs is a promising strategy for developing advanced pseudocapacitive electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the direct application of MOFs in electrochemistry is currently hindered by several issues, including agglomeration in the powder state and rather poor cycle performance. 23 The most conventional way to tackle this issue is to combine MOFs with other electrode-active materials such as MXenes, 24 MoS 2 , 25 carbon materials like carbon nanotubes (CNTs), 26 carbon fiber, 27 and metal hydroxides/oxides 28,29 with heteroatom doping to form composites. Thus, integrating MOFs with conductive 2D materials like graphene is a convenient approach that would help to revamp the overall energy storage performance by improving the electrode conductivity.…”
Section: Introductionmentioning
confidence: 99%